Transforming Conventional Switching Systems to Cost-Effective, Adaptable, Energy-Efficient Smart Switching Systems - Mishra, R. V.; Gupta, T.; Patel, A.; Kumar, R.; Kaur, I.; Batra, V. (Journal of Scientific Research, 2023)
Reducing energy consumption in the household and commercial sectors is a major global concern. Our objective is to develop a low-cost automation solution that will help improve adoption and reduce energy consumption. Proposed system has functionality that will help typical Indian households reduce electricity consumption in areas of infrequent usage such as stairs, and parking areas where manual switching of the electricity is difficult. In our proposed model, a manual switching system is replaced with a low-cost and adaptable smart automated switching system. Our design is based on the Passive/Pyroelectric Infrared Rays (PIR) motion-sensing mechanism where motion is used as a trigger to turn on/off electrical appliances. Detailed comparative analysis of daily energy usage of traditional switching with intelligent switching showed reduced electricity consumption by 33 %. Lower cost of equipment will increase the adoption of automated systems, leading to a reduction in electricity consumption. Further, a drop in energy consumption means reduced energy costs and less burden on the grid which leads to a clean environment.